VERTEBROBASILAR BLOOD FLOW IN GERIATRIC PATIENTS WITH HIP FRACTURES - AydÄ±n, Ekrem (MNJ (Malang Neurology Journal), 2021)
Background: Falls constitute a problem especially in individuals aged above 70 years in terms of fracture formation. Considering the etiology of falling, insufficiency of the blood flow which feeds the balance center in the brain may cause postural hypotension and vertigo and may lead to falling.Objective: In this study, we emphasized the importance of evaluating vertebrobasilar blood flow in the etiology of fractures in the elderly.Methods: This study was executed on 48 patients aged 70 years and older (28 females, 20 males, mean age 80.45), who were presented to the emergency department of DumlupÄ±nar University Evliya Ã‡elebi Training and Research Hospital with hip fractures resulting from a simple fall around where they live, diagnosed with hip fractures and treated via joint prostheses or different internal and external fixation methods. After the stabilization of the patients' postoperative fractures, the carotid artery lumen and blood flow, vertebral arterial lumen, diameter and blood flow were examined via doppler ultrasonography. The control group was comprised of 48 patients aged 70 years and older (26 females, 22 males, mean age 75.52 years) who were presented to the Polyclinic of Neurology for routine examination and had no falling and fracture history, and the carotid artery and vertebral artery examination of this group was also performed by the same radiologist via doppler ultrasonographyÂ Results: In individuals aged above 70 years, temporary cerebral blood flow disorders are more severe in those with vertebrobasilar insufficiency. This study was conducted between 2015-2016 on 48 patients aged 70 years and older (28 females and 20 males), who were presented to the emergency department of DumlupÄ±nar University Faculty of Medicine Training and Research Hospital and hospitalized due to hip fractures; the control group was comprised of 48 patients within the same age group, who were presented to the Polyclinic of Neurology with different complaints (26 females and 22 males).The vertebral arterial diameters and flow velocities of the patients were assessed via Doppler USG.Conclusion: The vertebral arterial diameters and flow velocities were found statistically lower in the patient group with fracture formation resulting from falling.We recommend taking precautions against the risk of falling in patients aged above 70 years who are found to have a flow decrease through carotid artery doppler USG at certain intervals.